2017
DOI: 10.1039/c7tb00134g
|View full text |Cite
|
Sign up to set email alerts
|

Anti-cancer activity of camptothecin nanocrystals decorated by silver nanoparticles

Abstract: CPT/Ag nanocrystals display extreme and broad-spectrum anti-cancer activity and high selectivity through a cooperation effect between CPT and AgNPs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 51 publications
1
24
0
Order By: Relevance
“…In on similar lines, Zhan et al 60 have reported camptothecin nanocrystals decorated with silver nanoparticles. Authors have reported excellent dispersion properties along with enhanced dissolution rate and cellular uptake.…”
Section: Parenteral Nanosuspensionmentioning
confidence: 73%
See 1 more Smart Citation
“…In on similar lines, Zhan et al 60 have reported camptothecin nanocrystals decorated with silver nanoparticles. Authors have reported excellent dispersion properties along with enhanced dissolution rate and cellular uptake.…”
Section: Parenteral Nanosuspensionmentioning
confidence: 73%
“…During selection of stabilizers several factors affect stability and particle size of the nanosuspension formulation viz . morphology of polymers, functional groups, hydrophilic or hydrophobic ratio in stabilizer molecule and molecular weight 59 , 60 . Polymer composition has the direct effect on the stability of nanosuspension.…”
Section: Parenteral Nanosuspensionmentioning
confidence: 99%
“…Auriga Modular Cross Beam workstation (Carl Zeiss, Inc.) was using with 1.5 kV accelerating voltage. The films were sputter coated with a conductive layer of gold palladium (Au/Pd) for 1.0 min for an approximately 15 nm coating [3] .…”
Section: Experimental Design Materials and Methodsmentioning
confidence: 99%
“…Quinoline compounds can induce and regulate some transcription factors to mediate apoptosis and metabolism, and inhibit the occurrence of cancer and tumors. In addition, quinoline compounds have been confirmed in related studies, which can be effective in inhibiting the development and progression of cancer and tumors …”
Section: Introductionmentioning
confidence: 91%
“…In addition, quinoline compounds have been confirmed in related studies, which can be effective in inhibiting the development and progression of cancer and tumors. [17][18][19][20][21] On the other hand, infectious diseases recently have faced major challenges in the world. The number of people with various plagues and deaths has increased considerably.…”
Section: Introductionmentioning
confidence: 99%